Reducing the hygroscopic swelling in MEMS sensor using different mold materials - Pinki Kumari; Kuldeep Singh; Anuj Singal (Institute of Advanced Engineering and Science, 2020)
Today, Hygroscopic swelling is one of the biggest challenging problem of Epoxy mold compound (EMC) in packaging with Microelectromechanical system (MEMS) devices. To overcome this hygroscopic swelling problem of EMC and guard the devices, MEMS devices are molded in this paper with different Mold Compound (MC) i.e. titanium and ceramic etc. during their interconnection with the board. Also, a comparatively performance analysis of this various mold compound with MEMS pressure sensor has been studied in this paper at 60% humidity, 140 mol/m3 saturation concentration and 25 oC. It was observed that hygroscopic swelling does not take place in the titanium mold compound. But, titanium is very costly so we have to consider something cheaper material i.e. ceramic in this paper. The Hygroscopic swelling in Ceramic Mold Compound after 1 year is nearly 0.05mm which is very less than epoxy.